PERANAN TENAGA ADMINISTRASI DALAM PENGELOLAAN ARSIP DI SMA YPKM MANADO - Jufrina Mandulangi; Altje Ellen Tuwaidan; Donny Taju; Jeaneta J Rumerung (Journal of Business Administration (JBA), 2023)
Archives are one of the important sources of information that can support changes in situations and conditions that develop quickly. In a school organization as an educational institution, information becomes a very important thing to support school activities in facing rapid change. In Law of the Republic of Indonesia Number 43 of 2009 concerning Archives, records management is carried out to ensure the correct availability of archives, fast archive services, proper use designation, presentation of information that can be presented in full, and clear evidence of responsibility.Proper management of school records will create the correct school administration, so as to ensure administrative safety and security to support productivity for the school. Archives have a very important role for schools.Administrative personnel are an element that must be considered by every school organization because it is directly related to the management of school archives. The administrative personnel in the school are very helpful in managing school archives. Lack of records management from administrative personnel can make rediscovery of records very difficult to do quickly and the increase in records along with the activities of an institution that is not followed by systematic storage will result in the accumulation of records. In the initial observations, researchers found problems in structuring school records that were still not organized, how to manage records that were still ineffective, the role of administrative personnel that was not careful. The purpose is to find out the arrangement of archives, records management and the role of administrative personnel in managing archives at SMA YPKM Manado. The type of research used is a qualitative method with data collection through observation, interviews and documentation.